Rare case of immune mediated cutaneous leucoclastic vasculitis with pancytopenia in a rheumatoid arthritis patient with chronic cytomegalovirus infection - Bajpai, Rashmi Gupta; Garg, Ayush (International Journal of Research in Medical Sciences, 2024)
Acute febrile illnesses with systemic involvement can present significant diagnostic and therapeutic challenges, particularly in patients with multiple comorbidities. This case report highlights a complex presentation of acute febrile illness with pancytopenia and immune-mediated cutaneous vasculitis in a patient with type II diabetes mellitus. A 52-year-old male with a known history of type II diabetes mellitus presented with fever, decreased oral intake, loose stools, oral ulcers, dysphagia, and rashes over the trunk and abdomen for four days. Upon admission to the ICU, extensive diagnostic evaluations were performed, revealing significant hematological, biochemical, and serological abnormalities. Imaging studies and histopathological examinations were conducted to further investigate the underlying etiology. Laboratory findings indicated pancytopenia, acute kidney injury, and hyperkalemia. Infectious disease workup was largely negative, except for a positive CMV IgG. Imaging studies revealed medical renal disease, and a skin punch biopsy confirmed cutaneous leukocytoclastic vasculitis. Bone marrow biopsy suggested bone marrow suppression. Multidisciplinary management, including dialysis, IV fluids, antibiotics, blood transfusions, steroids, and Ganciclovir, led to the patient’s gradual improvement and stabilization. The comprehensive diagnostic and therapeutic approach in this case underscores the importance of considering immune-mediated etiologies in patients with atypical presentations. Multidisciplinary collaboration was crucial in managing the multifaceted clinical condition of the patient. Early recognition and prompt multidisciplinary management are essential in similar cases. Extensive diagnostic evaluations should be performed to identify the underlying causes, and immune-mediated etiologies should be considered in complex presentations. Further research is recommended to explore optimal management strategies for such multifaceted conditions.